PENGARUH PERSEPSI KEMUDAHAN DAN PERSEPSI MANFAAT TERHADAP MINAT PENGGUNAAN SISTEM INFORMASI AKADEMIK BERBASIS WEB PADA MAHASISWA UNIVERSITAS MULIA - Luthfi Azmi; Prayoga, Prana Yudhistira; Riski Zulkarnain; Nasruddin Bin Idris (CV Mazaya Cahaya Utama, 2026)
The digital transformation toward the Smart Campus concept demands high academic data integrity, which relies heavily on user interaction with the system. This study adopts a data-driven analysis approach to evaluate user adoption patterns of the web-based Academic Information System (AIS) at Universitas Mulia. Utilizing the Technology Acceptance Model (TAM) as a predictive framework, this research aims to identify determinant variables influencing user interaction data flow. Data were collected from 31 active users and analyzed using multiple linear regression modeling. The model evaluation results indicate that perceived ease of use and perceived usefulness simultaneously provide high predictive accuracy for behavioral intention, with a coefficient of determination (R2) of 81.6%. These findings confirm that TAM variables are valid parameters for system requirement engineering. Implicatively, this study recommends integrating Artificial Intelligence features for service personalization and optimizing data architecture to support adaptive user experiences, thereby ensuring the sustainability of the academic data lifecycle.